The Effectiveness of Parenting Skills Training for Mothers on Academic Procrastination and Mother–Child Relationship Among Elementary School Students - Rahimi, Maliheh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effectiveness of a parenting skills training program for mothers on academic procrastination and mother–child interaction among elementary school students.Methods and Materials: This study was conducted using a quasi-experimental pretest–posttest design with a control group. The statistical population consisted of mothers of 10- to 12-year-old elementary school students in District 7 of Tehran during the 2018–2019 academic year. After applying the inclusion and exclusion criteria, 42 mothers were selected through convenience sampling and randomly assigned to the experimental and control groups (21 participants in each group). The research instruments included the Mother–Child Relationship Evaluation Scale (MCRE) and the Procrastination Assessment Scale for Students (PASS). The experimental group participated in a parenting skills training program for six weeks (one 90-minute session per week), whereas the control group received no intervention. Data were analyzed using univariate and multivariate analysis of covariance in IBM SPSS Statistics.Findings: The results of ANCOVA indicated that parenting skills training significantly reduced students’ academic procrastination (P < 0.001, F = 4.92, η² = 0.11). In addition, the results of MANCOVA demonstrated a significant difference between the two groups in mother–child interaction dimensions (P < 0.001, F = 10.44, η² = 0.55). Univariate analyses revealed that the intervention increased maternal acceptance (η² = 0.29) and reduced rejection (η² = 0.30) and overprotection (η² = 0.20). However, no significant difference was observed in the permissiveness dimension (P = 0.09).Conclusion: Parenting skills training is an effective intervention for improving the quality of the mother–child relationship and reducing academic procrastination among elementary school students. Implementation of this program in schools, counseling centers, and educational institutions may contribute to improved academic functioning and healthier parent–child interactions. Future studies are recommended to employ long-term follow-up assessments and larger sample sizes.